The Use of "Traditional Flip" Method in Teaching Writing: Exploring Students' Perceptions - Maharani, Suci (Prosiding University Research Colloquium, 2023)
The increasing of educational technology compels the educator to undergo a transformation. Teachers must design an innovative media and method in the learning process to attract students' interest and motivation. Flipped classroom is one of teaching methods which can be used in teaching learning process. There are several models of flipped classroom. One of the models which suitable with the writing skill is traditional flip. Traditional flip is simply front-loading a video of content followed by problems, activities, or writing in class based on that content (Cockrum, 2014) This study aimed to investigate the students’ perception about flipped classroom in writing class. The design of the study was qualitative study using purposive sampling technique. The data were collected using interview and questionnaire. Ten students of twelfth grade participated in this study based on their experience through flipped classroom in writing class. The finding indicated that there were seven benefits obtained by the use of flipped classroom. They were categorized in the term of flexibility, feedback, students prior knowledge, efficiently use time, community, and autonomous learning. Another finding was about the obstacles occurred in learning process including internet connection, difficulty in understanding the video, and the lack of giving a score.